Time-of-Flight measurements with a detector using a liquid Cherenkov radiator-prototype of a possible TOF detector for the Super-FRS at FAIR; Nuclear Instruments and Methods in Physics Research A; Vol. 923 - Kuzminchuk-Feuerstein N. A. Natalia Aleksandrovna; Bogdanov O. V. Oleg Viktorovich; Rozhkova (Fiks) E. I. Elena Ivanovna; Scheidenberger Ch. Christoph; Voss B. Bernd (2019, 2019)
Title screen